The paradoxes of posterity - Hoffmann, Benjamin, 1985- (The Pennsylvania State University Press, 2020)
"Examines the paradoxes inherent in the search for symbolic immortality, arguing that there is only one truly serious literary problem: the transmission of texts to posterity"--